Stress Testing MQTT Server for Private IOT Networks - Hijazi, Ghofran; Habaebi, Mohamed Hadi; Al-Haddad, Ahmed; Zyoud, Alhareth Mohammed (Polish Academy of Sciences, Committee of Electronics and Telecommunications, 2021)
The rapid development of the Internet of Things (IoT) and the wide area of application rise the IoT concept to be the future of the internet. Indeed, IoT environment has a special nature with a lot of constraints in term of resource consumption. Moreover, the data exchanged between things and the internet is big data. In order to achieve efficiency in IoT communication, many technologies and new protocols based on these technologies have been developed. This paper aims to study the performance of Message Queuing Telemetry Transport (MQTT) by implementing this protocol on test-bed network infrastructure and analyzing the performance properties such as delay, jitter, packet loss and throughput for real time and non-real time scenarios. Finally, future research issues in MQTT protocol are suggested.